Response Of Peanut Plants (Arachis Hypogaea L.) To Application Of Liquid Manure From A Mixture Of Banana Peels, Egg Shell And Seaweeds - Friza Elinda; Neta Febriza Agusmi; Fredrika Eliesti; Aulia Meyuliana; Muharama Yora (UNIVED Press, Dehasen University Bengkulu, 2022)
This research was conducted in Halaban-Panyakalan, Kubung District, Solok Regency, West Sumatra starting from November 2021 to March 2022. This study was designed and analyzed using a Randomized Block Design (RAK) with 6 treatments and 4 groups. Each treatment consisted of 3 polybags of sample plants, so that all 72 polybags of sample plants. The treatments given were P0: dose 0ml/polybag P1: dose 25ml/polybag P2: dose 50ml/polybag P3: dose 75ml/polybag P4: dose 100ml/polybag P5: dose 125ml/polybag. The observed data were analyzed for variance, if the calculated F was greater than the F table 5%, it was continued with the further test of Duncan's New Multiple Range Test (DNMRT) at a 5% significance level. Parameters observed were plant height, number of primary branches, age of flowering, number of pods and dry weight of seeds. The results of the research that have been carried out explain that there is a significantly different effect of giving POC a mixture of banana peels, egg shells, and seaweed on the parameters of flowering age by giving 125 ml of POC/polybag (P5). Furthermore, the parameters of plant height, number of primary branches, number of pods and seed dry weight showed no significant effect on the treatment given, so it was necessary to increase the dose of POC administration of a mixture of banana skin egg shell, and seaweed in order to get a better response. good for some of these parameters.